Applications of digital signal processing to audio and acoustics - Kahrs, Mark; Brandenburg, Karlheinz (The Springer International Series in Engineering and Computer Science, 1998)
In 1998 the main applications of audio DSP are high quality audio coding and the digital generation and manipulation of music signals. They share common research topics including perceptual measurement techniques and analysis/synthesis methods. Additional important topics are hearing aids using signal processing technology and hardware architectures for digital signal processing of audio. In all these areas the 1990s have seen a significant amount of application-oriented research.